Innovative work behaviour among Malaysian education officials: a MANOVA Analysis - Noraine Jamil,; Mohd Izham Mohd Hamzah,; Aida Hanim A. Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Organisations must adapt quickly and innovate to improve. Therefore, the goal of this study is to determine the level of Innovative Work Behaviour (IWB) of the State Education Official (SEO) in Malaysia from the dimensions of opportunity exploration, idea generation, idea promotion, idea realisation, and idea sustainability as well as to explore the differences in IWB of the SEO in Malaysia across demographic factors. Respondents represented every region of Malaysia. Analysis of data utilising quantitative research methods. To ensure regional representation, 450 SEO from Northern Region, Central Region, Southern Region, East Coast, and East Malaysia were selected via stratified random sampling and sent online structured questionnaires. The level of IWB was found to be very high (M=4.31, SD=0.51). The SEO's frequency of participation in governance, leadership, and educational management courses during the tenure at the State Education Department (SED) was found to be significant according to Multiple Analysis of Variance (MANOVA) results (Wilks’ λ= 0.939, F (15, 445) =1.878; p=0.022). However, the SEO IWB did not differ by age, position, experience, and academic credentials. The Ministry of Education (MOE) Malaysia and SED may leverage the results of this study to re-evaluate and redesign IWB concepts to improve educational management.